Comparison of Arrhythmia Detection by 24-Hour Holter and 14-Day Continuous Electrocardiography Patch Monitoring - Chua, Su-Kiat; Chen, Lung-Ching; Lien, Li-Ming; Lo, Huey-Ming; Liao, Zhen-Yu; Chao, Shu-Ping; Chuang, Cheng-Yen; Chiu, Chiung-Zuan (Acta Cardiologica Sinica, 2020)
Background: Although 24-hour Holter monitoring is routinely used for patients with suspected paroxysmal arrhythmia, its sensitivity in detecting such arrhythmias is insufficient. Methods: We compared a 14-day electrocardiography (ECG) monitor patch-a single-use, noninvasive, waterproof, continuous monitoring patch-with a 24-hour Holter monitor in 32 consecutive patients with suspected arrhythmia. Results: The 14-day ECG patch was well tolerated, and its rates of detection of relevant arrhythmias on days 1, 3, 7, and 14 were 13%, 28%, 47%, and 66%, respectively. The detection rate of paroxysmal arrhythmias was significantly higher for the 14-day ECG patch than for the 24-hour Holter monitor (66% vs. 9%, p ＜ 0.001). Among the 32 patients, 202 atrial fibrillation or atrial flutter episodes were detected in 6 patients (22%) with the 14-day ECG patch; however, only 1 atrial fibrillation episode was detected in a patient (3%, p ＜ 0.05) with the 24-hour Holter monitor. Other clinically relevant arrhythmias recorded on the 14-day ECG patch included 21 (65.5%) episodes of supraventricular tachycardia, 2 (6.3%) long pause, and 2 (6.3%) ventricular arrhythmias. The mean dermal response score immediately after removal of the 14-day ECG patch from the patients was 0.64, which indicated minimal erythema. Conclusions: The 14-day ECG patch was well tolerated and allowed for longer continuous monitoring than the 24-hour Holter monitor, thus resulting in improved clinical accuracy in the detection of paroxysmal arrhythmias. Future studies should examine the long-term effectiveness of 14-day ECG patches for managing selected patients.